Peran Etika dan Akhlak dalam Pendidikan Islam - Basori, Basori; Nadila Amri; Pajarni, Pajarni; Siti Nabila (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Islamic education emphasizes the development of high morals as the main goal in producing people who are morally ethical and intelligent. The foundation of character development through education that combines intellectual, spiritual, emotional, and social aspects is morality, as shown by the Prophet PBUH. Teachers play an important role in teaching moral principles to students and how to behave in a way that is in harmony with Islamic beliefs. It is anticipated that education based on morals and ethics will be able to create a generation that is able to handle the difficulties of the modern world with responsibility, justice, and empathy.